2010
DOI: 10.1088/0953-8984/22/34/345603
|View full text |Cite
|
Sign up to set email alerts
|

Anab initioevaluation of the local effective interactions in the NaxCoO2family

Abstract: We used quantum chemical ab initio methods to determine the effective parameters of Hubbard and t-J models for the Na(x)CoO(2) compounds (x = 0 and 0.5). As for the superconducting compound we found the a(1g) cobalt orbitals above the e'(g) ones by a few hundreds of meV due to the e'(g)-e(g) hybridization of the cobalt 3d orbitals. The correlation strength was found to increase with the sodium content x, whereas the in-plane AFM coupling decreases. The less correlated system was found to be the pure CoO(2), ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…), since it supports the Fermi level electrons 6,10 while the CoCa 2 O 3 subsystem was proved to be gapped. In addition, in the related Na x CoO 2 family the Fermi level properties were proved to be strongly dependant both on the doping 4 and on the local structural parameters 13 . The purpose of the present work will thus be to study the effect of the incommensurate modulations on the low energy degrees of freedom of the Ca 3 Co 4 O 9 system.…”
Section: Introductionmentioning
confidence: 99%
“…), since it supports the Fermi level electrons 6,10 while the CoCa 2 O 3 subsystem was proved to be gapped. In addition, in the related Na x CoO 2 family the Fermi level properties were proved to be strongly dependant both on the doping 4 and on the local structural parameters 13 . The purpose of the present work will thus be to study the effect of the incommensurate modulations on the low energy degrees of freedom of the Ca 3 Co 4 O 9 system.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that while the a 1g -only description is valid for large x, holes occupy both a 1g and e ′ g orbitals at small x [13], and the onsite Hubbard correlation U is x-dependent. Quantum chemical configuration interaction calculations [14] find larger a 1g − e ′ g separation than LDA calculations [2], and (ii) many-body approaches that take Coulomb hole-hole repulsion into account [15][16][17] do not find the e ′ g pockets on the Fermi surface predicted within LDA calculations.x-dependence has also been ascribed to differences in the potential due to Na layers [11,18]. Experimentally, Li x CoO 2 [19] and Bi "misfit" cobaltates [20] do not exhibit ion ordering but nevertheless exhibit very similar carrier concentration-dependence [19,20], suggesting that this dependence is intrinsic to the CoO 2 layers, with the interlayer potential playing a secondary role.In the present Letter we show that a simple and natural explanation of the carrier concentration-dependence emerges within a 1g -only as well as multiband extended Hubbard models.…”
mentioning
confidence: 99%
“…As in [16], we have ignored the Hund's rule coupling based on the very small hole occupation of e ′ g orbitals (see below). As both photoemission experiments [3][4][5] and many-body theories [14,15,17] find negligible role of e ′ g orbitals, we discuss the one-band limit of Eq. 1 first.…”
mentioning
confidence: 99%
“…
The OP4-(Li/Na)xCoO2 phase is an unusual lamellar oxide with a 1:1 alternation between Li and Na interslab spaces. In order to probe the local structure, electronic structure and dynamics, 7 Li and 23 Na magic angle spinning nuclear magnetic resonance (MAS NMR) spectroscopy were performed in complementarity to X-ray diffraction and electronic and magnetic properties measurements. 7 Li MAS NMR showed that NMR shifts result from two contributions: the Fermi contact and the Knight shifts due to the presence of both localized and delocalized electrons that is really unusual.
…”
mentioning
confidence: 99%
“…In order to probe the local structure, electronic structure and dynamics, 7 Li and 23 Na magic angle spinning nuclear magnetic resonance (MAS NMR) spectroscopy were performed in complementarity to X-ray diffraction and electronic and magnetic properties measurements. 7 Li MAS NMR showed that NMR shifts result from two contributions: the Fermi contact and the Knight shifts due to the presence of both localized and delocalized electrons that is really unusual. 7 Li MAS NMR clearly shows several Li environments indicating that, moreover, Co ions with different local electronic structures are formed, probably due to the arrangement of the Na + ions in the next cationic layer.…”
mentioning
confidence: 99%